2014
DOI: 10.3109/02770903.2013.878845
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator response as a hallmark of uncontrolled asthma: a randomised clinical trial

Abstract: BD response can be used as a reliable measure of asthma control. This study suggests that ACQ5 scores alone are not sufficient to fully assess asthma control, and that BD response should be included as an essential measurement in any algorithm of asthma control evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[5,12] Higher sputum eosinophils were consistently associated with significantly greater OCS response in five studies. [5,6,13,16,17] Similarly, a strong statistically-significant positive association between blood eosinophils and OCS response was reported in three studies. [5,6,18] Higher baseline FeNO was also associated with a stronger OCS response in three studies [5,17,18], although one reported inconclusive results.…”
Section: Correlates Of Ocs Responsementioning
confidence: 57%
See 4 more Smart Citations
“…[5,12] Higher sputum eosinophils were consistently associated with significantly greater OCS response in five studies. [5,6,13,16,17] Similarly, a strong statistically-significant positive association between blood eosinophils and OCS response was reported in three studies. [5,6,18] Higher baseline FeNO was also associated with a stronger OCS response in three studies [5,17,18], although one reported inconclusive results.…”
Section: Correlates Of Ocs Responsementioning
confidence: 57%
“…[5,11,15] In contrast, a single study reported a substantially higher mean baseline FEV1 among corticosteroid responders (74%) than non-responders (55%). [12] A lower FEV1/FVC ratio was associated with a stronger OCS response in two studies [5,13], with one reaching statistical significance. [5] Two studies reported that patients with greater bronchodilator reversibility exhibited a stronger OCS response [13,14], however a further two found little evidence of an effect.…”
Section: Correlates Of Ocs Responsementioning
confidence: 92%
See 3 more Smart Citations